Balancing numbers which are concatenations of three repdigits - Erduvan, F.; Keskin, R. (Carpathian Mathematical Publications, 2024)
In this study, it is shown that the only balancing numbers which are concatenations of three repdigits are 204 and 1189. The proof depends on lower bounds for linear forms and some tools from Diophantine approximation.